Examining the Validity of the Total Nutrient Index for Assessing Intakes of Nutrients From Foods, Beverages, and Dietary Supplements. (7th June 2021) - Cowan, Alexandra; Jun, Shinyoung; Tooze, Janet; Dodd, Kevin; Gahche, Jaime; Eicher-Miller, Heather; Guenther, Patricia; Bhadra, Anindya; Bailey, Regan
Abstract: Objectives: To develop and validate the total nutrient index (TNI), a nutrient-based scoring system that assesses nutrient exposures from foods/beverages and dietary supplements (DS). Methods: The TNI includes 8 shortfall micronutrients identified in the Dietary Guidelines for Americans: calcium, magnesium, potassium, choline, and vitamins A, C, D, E. Predicted usual intake is expressed as a percentage of the appropriate Recommended Dietary Allowance or Adequate Intake and truncated at 100 to compute component scores. The average of the component scores yields the total TNI score (range 0–100). Usual intakes from foods/beverages and DS of U.S. adults (≥19y) were estimated using a multivariate extension of the National Cancer Institute method. Data sources were two 24-hour recalls and a questionnaire/in-home inventory on DS use, collected in the 2011–2014 National Health and Nutrition Examination Survey (NHANES) (n = 9, 954). Concurrent criterion validity was evaluated by comparing TNI scores between subpopulations with known differences in diet quality and by correlating component scores for vitamins A, C, D, and E with biomarker data. Due to data availability, biomarker analysis for vitamins A, C, and E used data from 2003–2006 NHANES (N = 8, 861). Convergent validity was determined by correlating the TNI with the Healthy Eating Index (HEI-2015). Results: The estimated mean total TNI score was 75.4; the same index calculated using foods/beverages only was 69.0. The TNI scores were significantly different (p < 0.001) for DS-users (83.5) vs. non-users (67.1), non-smokers (76.8) vs. smokers (70.3), and by food security status (food-secure: 76.6 vs. food-insecure: 69.1). The Pearson correlation of the TNI and HEI-2015 total score was 0.48, suggesting that the TNI captures dimensions of nutrient intake that are correlated with but distinct from those captured with the HEI-2015. Correlations of component scores with the available biomarkers ranged from 0.12 (α-tocopherol) to 0.36 (25(OH)D) and were all < 0.10 when DS were not included. Conclusions: The TNI identifies total usual intake of shortfall nutrients and extends existing measures of diet quality by including nutrients obtained from DS. Tests of validity suggest the TNI is an effective tool in assessing total nutrient exposures of shortfall nutrients among U.S. adults. Funding Sources: National Institutes of Health.